PENGGUNAAN PUPUK ORGANIK RIBON ATOM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT - Murdaningsih, Murdaningsih (Agriculture Faculty of Flores University, 2010)
Growth and tomato crop production influenced by the fertility of the land, which represents media grow the crop. Result of research indicates that usage of Ribon atom with the make-up of dose has an effect on positive to component growth of the crop, component produce and also fertility of the land. At the growth of crop posed at by is a high crop, wide leaf, PGR, LAI, LAD, and of LAR but dose 4 lt/ha not differ reality with dose 5 lt/ha and 6 lt/Ha. While component product that is the amount of fruit, heavy crop pear and pear weight set of wide, where dose 2 lt/ha does not differ reality with dose 3 lt/ha, 4/lt ha, 5 lt/ha and 6 lt/ha. As for its influence to the fertility of the land that is happened the make-up of contact of P available inland become to mount (Veri High).